215k views
3 votes
MAJOR HELPP!!!!!!!!!!! Picture Below guyyss! oof this is hard

MAJOR HELPP!!!!!!!!!!! Picture Below guyyss! oof this is hard-example-1
User Mstrobl
by
4.7k points

2 Answers

4 votes
93 is the answer.

To find the answer, we can first put x=8 and y=3 into the equation:

y^2 + 6(x + 3×2)
=3^2 + 6(8+3×2)

We can them proceed to calculate by doing the multiplications in the first steps:

=9 + 6(8+6)
=9 + 6×14
=9 + 84
=93

Therefore, the answer is 93.

Hope it helps!
User Dfmiller
by
5.4k points
0 votes

Answer:

93

Explanation:

Use PEMDAS and plug in the values for x and y. So replace x with 8 in the parenthesis, resulting in (8+2x3) since you do multiplication before addition, it would be 8+6 equaling 14. 14 would be multiplied by 6, so it would be 84, but do not forget the y^2, which would be 3^2 and since 3x3 is 9, you would add 9 to 84

User Maksim Kalmykov
by
4.9k points